Factors Affecting the Profitability of Insurance Companies in Albania - Kripa, Dorina; Msc. Dorina Ajasllari, (European Journal of Multidisciplinary Studies, 2016)
Good performance of a company determines the position of the company in its market and the growth and consolidation of the market, giving as result the development of the economy as a whole. The importance of this topic further enhanced when dealing with insurance companies because: 1) insurance companies’ transfers risk in the economy 2) provide a mechanism to promote savings 3) promote investment activities. The growing importance of insurance companies in Albania and the importance of profitability as one of the key performance metrics of a company are the reasons why we decide to write this paper. The variation of profits between insurance companies over the years, within a country, leads to believe that internal factors play a major role in determining profitability. We have taken under study the impact of growth rate, liabilities, liquidity, fixed assets, volume of capital and company size on the profitability of insurance companies. The methodology used is based on quantitative methods and the data are provided by reliable sources such as annual reports of insurance companies’, FSA reports and NRC . We have taken under study 7 companies, including non-life and life insurance companies, from 2008- 2013. The results of the paper show that factors such as growth rate, liabilities, liquidity and fixed assets are the main factors affecting the profitability of insurers, where the growth rate is positively associated with profitability, while liabilities, liquidity and fixed assets are negatively correlated. Company size and the volume of capital are positively correlated with the profitability of insurance companies’, but their impact is statistically insignificant.
Keywords: Insurance, profitability, correlation